2015
DOI: 10.1016/j.juro.2015.03.110
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Targeted vs Empirical Antibiotic Prophylaxis to Prevent Sepsis from Transrectal Prostate Biopsy: A Retrospective Analysis

Abstract: The targeted prophylaxis protocol enabled physicians to avoid using more than 1 broad-spectrum empirical antibiotic while simultaneously achieving an overall rate of sepsis similar to the rate seen with empirical prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 19 publications
3
38
0
1
Order By: Relevance
“…Taylor et al [29] showed a non-statistically significant reduction in the frequency of sepsis using targeted prophylaxis with rectal culture versus standard prophylaxis (0 vs. 2.6%, p = 0.12). Liss et al [30] reported similar findings in a retrospective analysis of 5,355 prostate biopsies. The incidence of post-PB sepsis between the empirical versus targeted prophylaxis group was not significantly different (0.56 vs. 0.44%, p = 0.568), however, targeted therapy prevented the use of more than one broad-spectrum empirical antibiotic.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Taylor et al [29] showed a non-statistically significant reduction in the frequency of sepsis using targeted prophylaxis with rectal culture versus standard prophylaxis (0 vs. 2.6%, p = 0.12). Liss et al [30] reported similar findings in a retrospective analysis of 5,355 prostate biopsies. The incidence of post-PB sepsis between the empirical versus targeted prophylaxis group was not significantly different (0.56 vs. 0.44%, p = 0.568), however, targeted therapy prevented the use of more than one broad-spectrum empirical antibiotic.…”
Section: Discussionsupporting
confidence: 54%
“…The rate of FQ-resistance in patients with pre-PB rectal culture ranges between 3.7 and 25% [30,31,32,33]. In our study, FQ-resistance was 45.62%.…”
Section: Discussionsupporting
confidence: 45%
“…Loeb et al indicated that men undergoing TRUSP-Bx were 2.26 times more likely to be hospitalized for infectious complications comparing to randomly selected controls [1]. Liss et al [19] concluded that their targeted prophylaxis protocol, including rectal cultures performed before transrectal prostate biopsy, enabled physicians to avoid using more than one broad-spectrum empirical antibiotic, while achieving an overall rate of sepsis similar to the rate seen with empirical prophylaxis. One of our patients died in the ICU due to multi-resistant E. coli septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…The California study compared targeted prophylaxis to empirical prophylaxis, which included both single-agent and augmented approaches (75% single agent and 25% augmented). No significant decrease in sepsis postintervention was observed, even when single-agent empirical prophylaxis was considered separately from augmented prophylaxis (30). Many smaller studies have shown a trend toward reduction but did not reach statistical significance, as they may not have been powered adequately to detect differences.…”
Section: How Do Augmented and Targeted Prophylaxes Affect Infection Rmentioning
confidence: 94%
“…Two of the largest studies to address these questions were quality improvement initiatives in the state of Michigan and urology departments in Southern California that evaluated infection rates following a quality intervention (17,30). The Michigan study demonstrated a 53% decrease in biopsy-infection-related hospitalizations for the combined intervention of either augmented or targeted prophylaxis compared to the standard prophylaxis chosen by the physician (17).…”
Section: How Do Augmented and Targeted Prophylaxes Affect Infection Rmentioning
confidence: 99%